If it's not what You are looking for type in the equation solver your own equation and let us solve it.
=4Y(2Y+3)
We move all terms to the left:
-(4Y(2Y+3))=0
We calculate terms in parentheses: -(4Y(2Y+3)), so:We get rid of parentheses
4Y(2Y+3)
We multiply parentheses
8Y^2+12Y
Back to the equation:
-(8Y^2+12Y)
-8Y^2-12Y=0
a = -8; b = -12; c = 0;
Δ = b2-4ac
Δ = -122-4·(-8)·0
Δ = 144
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$Y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$Y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{144}=12$$Y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-12)-12}{2*-8}=\frac{0}{-16} =0 $$Y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-12)+12}{2*-8}=\frac{24}{-16} =-1+1/2 $
| x-4-7x=-3x-7+8 | | u/7=7 | | 40=7x+19 | | 5/4-x-3/2=2(7x/4+5/4) | | 2m+7=37 | | 8x=2(4+3x) | | 9x+6-4x=-5x-15+x | | 6x+23=3x+63 | | 8(7x)=145 | | -7x=20=118 | | 6x+64=90 | | 4/x+6=2/x-6 | | 2(x-5)-4=22 | | -7+x/6=7x/2-5/3 | | u+18=7u | | d2+7d+7=0 | | 3-3x=45 | | X+4x=4x+1 | | x-6.8=14.7 | | 5y÷2=15 | | 7.50=15/n | | 6/3r=-7/2 | | 3+2x+(-34)=11 | | t+52=3 | | 3(4x+4)+5(2x-3)=-47 | | z-1/3=1/2/3 | | -(2x+10)=90 | | x+(2x-5)=130 | | b+42=3b | | 3x-8+4x=2x+18-6x | | 3x^2+5x+56=0 | | 9(f-94)=45 |